RANCANG BANGUN SISTEM MONITORING PRODUKSI MADU DAN HASIL SAMPING PADA FLOW-HIVE SYSTEM BERBASIS INTERNET OF THINGS - Naudy, Ayliefia Ramadhan; Nurussa’adah, n/a; Razak, Angger Abdul (Jurnal Mahasiswa TEUB, 2024)
Honey is a non-wood forest product derived from bees, with Indonesian honey production in 2022 reaching 189,780 litersannually, while the demand ranges from 5,000 to 15,000 tons per year based on a per capita consumption of 30 g/year. A primar y issue in conventional beekeeping is the alteration in honey quality due to contamination during post-harvest extraction processes. Beekeepers require an effective and flexible solution to address this problem. The Flow-Hive system, an Australian innovation, utilizes partial split cell technology with artificial combs, significantly differing in yield compared to conventional methods. Annually, conventional honey production yields an estimated net profit of 1,649.08 USD. The integration of IoT technology in the Flow-Hive system enhances monitoring efficiency and reduces bee stress by minimizing human contact. The IoT-based Flow-Hive monitoring system via smartphone includes honey weight measurement using a Load Cell HX711 sensor (up to 5 kg) with an accuracy of 99.8%, and by-product volume measurement using an ultrasonic HC SR04 sensor with an accuracy of 98.71%. The ESP32 microcontroller processes sensor data for display on an LCD and transmits it to the Blynk application, enabling real-time monitoring and data collection with 100% accuracy. Linear regression analysis indicated that honey production reached 3 kg on day 550, and by-product production peaked on day 9, with prediction accuracies of 99.90% and 90.11%, respectively. Keywords: Flow-hive system, Monitoring, Sensor, Honey, and Internet of Things